Malnutrition and the food crisis on the hope of life of the Venezuelans (Revista Venezolana de Salud Pública, 2018)
Malnutrition and the food crisis are facts that affect the majority of people living in Venezuela; this situation has been mentioned in this magazine on several occasions through research articles, as a public health problem. On the other hand, the Caritas Organization of Venezuela, estimates that in our country 280,000 children could die from malnutrition. In this sense, the studies reveal that during the year 2017, between five and six children died weekly due to lack of food, and that at least 33% of the child population had a delay in their growth1. In addition, malnutrition increases the risk of infections, viruses and bacteria, which leads to the appearance of various diseases typical of poorly nourished people; Among them are infections that in some cases, especially children, require prolonged hospital stays that affect their psychomotor development. One is Kwashiorkor, common in babies and children suffering from a strong protein deficiency; Its consequences are diarrhea, edema, liver damage and lack of growth. On the other hand, Marasmus is a type of malnutrition that occurs when the person's diet is insufficient in both calories and proteins; children with this malnutrition are very thin, with enlarged eyes
Keywords: Venezuela; nutrition